Pengaruh Penggunaan Tepung Daun Belimbing Manis sebagai Substitansi Pakan Kelinci terhadap Berat Badan - Roji, Fadilla; Hasibuan, Febry Ramadhani; Siregar, Abdul Hasym Mazhurin; Jupani, Indah Amelia (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Rabbit (Oryctogalus cuniculus) is a livestock that has great potential as a pet or ornamental animal, producing meat and skin/hair (Raharjo et al. 2001). The development of rabbit farming in Indonesia has been growing in the community because it is easy to maintain, relatively does not require large capital, the business cycle is relatively fast, produces a variety of products, there are not many competitors, can utilize narrow land and can use agricultural waste as feed. This study aims to analyze the impact of the feed given to rabbits, to analyze what content is in starfruit leaf flour and to facilitate the selection of alternative feeds such as leaves. The research method used was to analyze how the effect of the ratio of regular feeding and using starfruit leaves (Averrhoa carambola L.) on body weight in rabbits (Oryctogalus cuniculus). Keywords: Rabbit , Feed , Comparison